2019
DOI: 10.1074/mcp.ra118.001253
|View full text |Cite
|
Sign up to set email alerts
|

Hdac4 Interactions in Huntington's Disease Viewed Through the Prism of Multiomics

Abstract: The histone deacetylase Hdac4 is known to contribute to the progression of Huntington's Disease (HD), but the underlying mechanisms remain unknown. Here, we defined the endogenous interactome of Hdac4 in the brain of HD mouse models, characterizing their polyQ-and age-dependence in affected tissues. Further integration with proteome and transcriptome data sets reveals the diseaseinduced enhancement of Hdac4 interactions with vesicular sorting proteins, including the WASH complex. This may contribute to the kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 80 publications
1
22
0
Order By: Relevance
“…Characterization of interactome of endogenous HDAC4 in brains of HD mouse models revealed interaction of HDAC4 with Wiskott-Aldrich Syndrome Protein and SCAR Homolog (WASH) complex. This study confirmed the role of HDAC4 in progression of HD (Federspiel et al, 2019).…”
Section: Huntington Diseasesupporting
confidence: 85%
“…Characterization of interactome of endogenous HDAC4 in brains of HD mouse models revealed interaction of HDAC4 with Wiskott-Aldrich Syndrome Protein and SCAR Homolog (WASH) complex. This study confirmed the role of HDAC4 in progression of HD (Federspiel et al, 2019).…”
Section: Huntington Diseasesupporting
confidence: 85%
“…In a previous study, end-stage disease occurred much earlier, and the range of neurological phenotypes was more extensive in R6/2 mice with aggregate pathology in both the nucleus and cytoplasm, as compared to those with comparable aggregation occurring in the nucleus only ( Benn et al , 2005 ). In keeping with this, heterozygosity for HDAC4, a cytoplasmic protein that interacts with HTT ( Mielcarek et al , 2013 ; Federspiel et al , 2019 ), delayed aggregation in the cytoplasm, improved behavioural phenotypes, and delayed end-stage disease in R6/2 mice, whilst the levels of nuclear aggregation and transcriptional dysregulation were unchanged ( Mielcarek et al , 2013 ).…”
Section: Discussionmentioning
confidence: 71%
“…protein function. Federspiel et al (11) used a multi-omics approach to uncover the function of histone deacetylase 4 (Hdac4) in the context of Huntington's disease (HD) progression. The authors characterized the interactomes of endogenous Hdac4 in the brains of HD mouse models with wild type and mutant forms of the huntingtin (Htt) gene at both presymptomatic and symptomatic ages.…”
mentioning
confidence: 99%